2006
DOI: 10.1021/es051780k
|View full text |Cite
|
Sign up to set email alerts
|

Nitroaromatic Reduction Kinetics as a Function of Dominant Terminal Electron Acceptor Processes in Natural Sediments

Abstract: The reductive transformation of p-cyanonitrobenzene (pCNB) was investigated in laboratory batch slurries exhibiting dominant terminal electron accepting processes (TEAPs). Pseudo-first-order rate constants (k(obs)) were measured for the reduction of pCNB in nitrate-reducing, iron-reducing, sulfate-reducing, and methanogenic sediment slurries. Reduction was extremely slow in nitrate-reducing slurries but increased in slurries exhibiting TEAPs with significant concentrations of solution phase Fe(ll). As the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…We attribute these differences to changes in the speciation of the metal complexes resulting from alterations in solution pH and carbonate concentration as a consequence of Ar-sparging. Although iron sulfide complexes and other dissolved sulfur species have been measured by others within this half-cell potential range (À0.1 to À0.7 V) in natural pore waters (Rozan et al, 2000), the neutral pH of unpurged pore waters (range 6.7-7.6), high dissolved Fe(II) content, lack of characteristic sulfidic odor and lack of black precipitate (indicative of the presence of iron sulfides, per Hoferkamp and Weber (2006)) indicated that the contribution of inorganic sulfur species towards OWC pore water chemistry is likely to be minimal.…”
Section: Pore Water Redox Chemistrymentioning
confidence: 90%
See 3 more Smart Citations
“…We attribute these differences to changes in the speciation of the metal complexes resulting from alterations in solution pH and carbonate concentration as a consequence of Ar-sparging. Although iron sulfide complexes and other dissolved sulfur species have been measured by others within this half-cell potential range (À0.1 to À0.7 V) in natural pore waters (Rozan et al, 2000), the neutral pH of unpurged pore waters (range 6.7-7.6), high dissolved Fe(II) content, lack of characteristic sulfidic odor and lack of black precipitate (indicative of the presence of iron sulfides, per Hoferkamp and Weber (2006)) indicated that the contribution of inorganic sulfur species towards OWC pore water chemistry is likely to be minimal.…”
Section: Pore Water Redox Chemistrymentioning
confidence: 90%
“…Mn(II) reaches a maximum around 6 cm depth, and either remains constant or decreases slightly at depths >6 cm. Although Mn(II) is present in all samples, previous work with NAC probe compounds in natural systems have emphasized the importance of dissolved Fe(II) on NAC reactivity under iron-reducing conditions (Heijman et al, 1995;Rü gge et al, 1998;Hoferkamp and Weber, 2006). Thus, we expect dissolved Fe(II) to act as an important redox-active metal capable of participating in electron-transfer reactions in OWC sediment pore waters.…”
Section: Pore Water Redox Chemistrymentioning
confidence: 92%
See 2 more Smart Citations
“…Studies of model and natural sediment systems have shown that the reductive transformation of nitroaromatic compounds (NACs) under anaerobic conditions occurs primarily through abiotic processes rather than biotransformation [16]. Elovitz and Weber [15] found that over 95% of 25 M TNT was lost from the aqueous phase of an aerobic sediment-water system within the first 2 h, with 50% being removed from the solution by sorption.…”
Section: Introductionmentioning
confidence: 99%